Unveiling the impact of non-coding RNAs on virus-induced cellular autophagy: roles and research advances - Yu, Ming; Yi, Ying; Yang, Honglin; Zhang, Yi (Frontiers in Microbiology, 2025)
Autophagy is the process by which cells degrade and recycle damaged organelles and macromolecules by forming autophagosomes. This process is closely related to the maintenance of cellular homeostasis, ontogeny, and the occurrence and development of various diseases. Non-coding RNAs (ncRNAs) are a class of RNA molecules that do not encode proteins but play crucial roles in regulating gene expression. Numerous studies have demonstrated that ncRNAs are involved in regulating autophagy, and accumulating scientific evidence suggests that ncRNAs play an essential role in virus-induced cellular autophagy. ncRNAs affect autophagy by participating in the autophagy regulatory network, mediating the transcriptional and post-transcriptional regulation of autophagy-related genes. This review aims to explore the role of ncRNAs in autophagy induced by viral infection and analyze the relevant molecular regulatory mechanisms underlying autophagy. By examining the content above, we speculate that targeted regulation of ncRNAs can affect autophagy induced upon viral infection, thereby achieving antiviral effects and host cell protection.